2022
DOI: 10.1007/s00701-022-05382-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for degenerative cervical myelopathy in patients with rheumatoid arthritis and ankylosing spondylitis: a nationwide registry-based study with patient-reported outcomes

Abstract: Purpose To compare patient-reported outcomes (PROMs) following surgery for degenerative cervical myelopathy (DCM) among patients with rheumatoid arthritis (RA) or ankylosing spondylitis (AS) versus those without rheumatic diseases. Methods Data were obtained from the Norwegian Registry for Spine Surgery. The primary outcome was change in the Neck Disability Index (NDI) at 1 year. Secondary endpoints included the European Myelopathy Score (EMS), quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…T he available medical literature has shown that surgical procedures can improve functional status and quality of life by relieving spinal cord compression, especially in multilevel degenerative cervical myelopathy (MDCM). [1][2][3][4][5][6][7][8][9] Currently, anterior cervical spinal fusion surgery including anterior cervical discectomy fusion (ACDF) and anterior cervical corpectomy fusion (ACCF) are routinely used in patients with MDCM. Although ACDF can alleviate the compression by removing the disc and osteophyte directly.…”
Section: Introductionmentioning
confidence: 99%
“…T he available medical literature has shown that surgical procedures can improve functional status and quality of life by relieving spinal cord compression, especially in multilevel degenerative cervical myelopathy (MDCM). [1][2][3][4][5][6][7][8][9] Currently, anterior cervical spinal fusion surgery including anterior cervical discectomy fusion (ACDF) and anterior cervical corpectomy fusion (ACCF) are routinely used in patients with MDCM. Although ACDF can alleviate the compression by removing the disc and osteophyte directly.…”
Section: Introductionmentioning
confidence: 99%